Analysis of the Influence of Profitability Ratio on the Capital Structure of Bank Central Asia Tbk (2009-2020) - Hamdana, Alief Afriya Gardha; Faishal Fadli (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study discusses financial performance as an indicator of a bank's success. Important factors in assessing profitability include skills, resources, and the company's capital structure. Bank Central Asia (BCA), a leading bank in Indonesia, was chosen as the focus of the study. This research examines the influence of profitability ratios, such as ROA and ROE on the capital structure through DER from 2009 to 2020. The study employs the theory of capital structure, which is used to understand the use of debt and equity in maximizing a company's value. To understand the correlation between variables, the vector error correction model method was selected to comprehend the long-term and short-term relationships among time series variables. Abstrak Penelitian ini membahas kinerja keuangan sebagai indikator keberhasilan bank. Faktor penting dalam menilai profitabilitas adalah keterampilan, sumber daya, dan struktur modal perusahaan. Bank Central Asia (BCA), bank terkemuka di Indonesia, dipilih sebagai fokus penelitian. Penelitian ini melihat pengaruh rasio profitabilitas melalui ROA dan ROE dengan struktur modal melalui DER sejak tahun 2009 hingga 2020. Penelitian ini menggunakan teori modal sendiri di mana teori ini digunakan untuk memahami penggunaan utang dan ekuitas dalam memaksimalkan nilai perusahaan. Dalam mengetahui korelasi antar variabel dipilihnya metide model koreksi error vektor yang ditujukan untuk memahami hubungan jangka panjang dan pendek antar variabel waktu.